Family History of Alzheimer's Disease and Cortical Thickness in Patients With Dementia. (August 2016) - Ganske, Steffi; Haussmann, Robert; Gruschwitz, Antonia; Werner, Annett; Osterrath, Antje; Baumgaertel, Johanna; Lange, Jan; Donix, Katharina L.; Linn, Jennifer; Donix, Markus
A first-degree family history of Alzheimer's disease reflects genetic risks for the neurodegenerative disorder. Recent imaging data suggest localized effects of genetic risks on brain structure in healthy people. It is unknown whether this association can also be found in patients who already have dementia. Our aim was to investigate whether family history risk modulates regional medial temporal lobe cortical thickness in patients with Alzheimer's disease. We performed high-resolution magnetic resonance imaging and cortical unfolding data analysis on 54 patients and 53 nondemented individuals. A first-degree family history of Alzheimer's disease was associated with left hemispheric cortical thinning in the subiculum among patients and controls. The contribution of Alzheimer's disease family history to regional brain anatomy changes independent of cognitive impairment may reflect genetic risks that modulate onset and clinical course of the disease.